Critical Synthesis Package: Advanced Cardiac Life Support (ACLS) Checklists for Simulation-Based Education - Shilpa Brown (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health sciences education for the Advanced Cardiac Life Support (ACLS) Checklists for Simulation-Based Education, and (2) a copy of the ACLS Checklists for Simulation-Based Education instrument developed by Diane Wayne, MD. The ACLS Checklists for Simulation-Based Education is a curriculum of the six most common ACLS conditions seen by internal medicine residents at Northwestern University. These include ventricular fibrillation, asystole, ventricular tachycardia, pulseless electrical activity, supraventricular tachycardia, and bradycardia. The PGY2 internal medicine residents engaged in three 2-hour sessions. The first session included a pretest on each of the six ACLS scenarios and the second included deliberate practice with checklists, as well as simulation and feedback from instructors. Session three contained a posttest. The internal medicine residents significantly improved their scores on each of the six ACLS scenarios and retained those skill sets for at least 14 months using the ACLS Checklists compared to the traditional American Heart Association ACLS 1-day course alone. Limitations to consider for this curriculum include using computer simulators for both education and testing hence possibly confounding the events. Also, one cannot generalize these results to clinical practice due to the infrequency of actual events. In addition, this instrument was studied using a case-control perspective design rather than prospective randomized design. Factors such as input or cuing from other members of the simulation team may influence adherence to guidelines thereby also altering the data. Although this curriculum is currently being used solely in one training program at a single academic center with a small sample size, the use of this curriculum supports its educational impact on ACLS skills. This curriculum will allow educators at other institutions to recreate this simulation-based educational program in order to improve ACLS skills among their residents and to provide improved care for patients with ACLS at their institutions.